Remuneração Executiva e Desempenho Organizacional Multidimensional em Empresas Brasileiras - Duarte, Denize Lemos (2023)
Global events related to poor performance and, ultimately, the collapse of large corporations have triggered an imperative need to strengthen Corporate Governance, both in developed and emerging economies. The issue of Corporate Governance has gained significant prominence in the capital markets, attracting attention from the local and international public in light of waves of corporate scandals. In this context, Corporate Governance must incorporate mechanisms that ensure a suitable return on investment to capital providers. Therefore, this research seeks to deepen the understanding of the relationship between executive compensation, one of the key mechanisms of Corporate Governance, and organizational performance. Thus, it is relevant to investigate the relationship of this mechanism, executive compensation, which affects capital allocation and organizational performance. Studies exploring the association between these constructs provide valuable insights into understanding agency dilemmas in the pursuit of value maximization and business continuity. In this perspective, the primary purpose of this research is to investigate the relationship between executive compensation and the performance of Brazilian publicly traded companies, both internationalized through the issuance of American Depositary Receipts (ADRs) and non-internationalized, evaluating this relationship in the context of the level of Corporate Governance and from the perspective of Agency Theory. This analysis is conducted with a detailed focus on internationalized companies and non-internationalized ones, considering the listing segments that distinguish the highest level of Corporate Governance among publicly traded companies listed on the Brazilian stock exchange, Brazil, Bolsa e Balcão (B3), during the period from 2010 to 2022. To achieve this objective, this research employed descriptive statistics, the Data Envelopment Analysis (DEA) technique, Multiple Linear Regression models, and Logistic Regressions. The main findings indicate that in the model comparing internationalized and non-internationalized companies, internationalized companies tend to exhibit much superior performance. Fixed compensation has been significant and positive in internationalized companies, possibly due to efforts to retain talent in the face of the challenges of dual listing. However, short-term and long-term variable compensations did not show significance in the model. In the model where the Total Compensation of the Statutory Board was the dependent variable, a significant and positive relationship was identified with market value in the general model, covering all the companies surveyed. In the model where performance was the dependent variable, none of the compensation types showed a significant relationship, except for fixed compensation, which exhibited an inverse relationship, suggesting that superior performance is associated with lower fixed compensations, in line with previous studies. Unexpectedly, companies with a higher level of Corporate Governance, specifically those listed on the Novo Mercado, showed inferior performance despite receiving higher compensations. Executive compensation modalities, including fixed compensation, short-term variable, and equity-based compensation, proved significant and positive for Novo Mercado companies and did not yield a superior market value, contradicting previous research. This study contributes to understanding the complex relationship between executive compensation, organizational performance, internationalization, and Corporate Governance in the Brazilian context, emphasizing the importance of considering additional variables and exploring different perspectives to comprehend business dynamics. Future research can expand these analyses, highlighting the DEA technique approach, and investigate other variables that may influence this relationship.